2016
DOI: 10.1080/02640414.2016.1189588
|View full text |Cite
|
Sign up to set email alerts
|

Age-ordered shirt numbering reduces the selection bias associated with the relative age effect

Abstract: When placed into age groups for junior sporting competition, the relative differences in age between children leads to a bias in who is evaluated as being talented. While the impact of this relative age effect (RAE) is clear, until now there has been no evidence to show how to reduce it. The aim of this study was to determine whether the selection bias associated with the RAE could be reduced. Talent scouts from an elite football club watched junior games and ranked players on the basis of their potential. Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
91
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 29 publications
2
91
1
4
Order By: Relevance
“…Similarly, scouting biases towards relatively older players can be mitigated through the use of age-ordered shirt numbers (65). These strategies and perhaps others attempt to address the relative age bias in athlete recruitment.…”
Section: Fitness Z-scores For U12smentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, scouting biases towards relatively older players can be mitigated through the use of age-ordered shirt numbers (65). These strategies and perhaps others attempt to address the relative age bias in athlete recruitment.…”
Section: Fitness Z-scores For U12smentioning
confidence: 99%
“…These strategies and perhaps others attempt to address the relative age bias in athlete recruitment. The effectiveness of such strategies may be limited, however, as variation in actual maturity status is not accounted for, as noted in the report (65).…”
Section: Fitness Z-scores For U12smentioning
confidence: 99%
“…A related remedy could be to present information about student age properly to teachers. For example,Mann and van Ginneken (2017) show that age-ordered shirt numbering could eliminate selection bias associated to the RAE in youth football.…”
mentioning
confidence: 99%
“…Therefore, in general coaches in youth soccer should be aware of this fact, and, especially, coaches in Norway should for sure be aware of the policy of NFF which clearly states that coaches shall not equal present level of performance with the potential of a player (NFF, 2018). Nevertheless, talent identification is a complicated matter that requires coaches to make subjective judgments of talent that are likely to be influenced by relative age (Mann & van Ginneken, 2017;Romann & Cobley, 2015). To minimise the selection-induced RAE one organizes tournaments in Norway for future teams that only consist of late matures or one use 6-months bands rather than 12-months age categories (NFF, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…To minimise the selection-induced RAE one organizes tournaments in Norway for future teams that only consist of late matures or one use 6-months bands rather than 12-months age categories (NFF, 2018). Another possible approach is to age-order the shirt-numbering of the players, and in a study conducted by Mann & van Ginneken (2017) they demonstrated that the selection bias found as a result of the RAE can be eliminated by ensuring that the shirt numbers worn by junior athletes during competition are ordered according to their age. The finding of this study offers organisations and coaches a simple and practical means of reducing the selection bias associated with RAE in junior team sport.…”
Section: Resultsmentioning
confidence: 99%